IL-4Rα on dendritic cells in neonates and Th2 immunopathology in respiratory syncytial virus infection. Issue 1 (7th April 2017) - Shrestha, Bishwas; You, Dahui; Saravia, Jordy; Siefker, David T; Jaligama, Sridhar; Lee, Greg I; Sallam, Asmaa A; Harding, Jeffrey N; Cormier, Stephania A
Abstract : Elevated IL-4Rα expression on neonatal CD11b + mDCs promotes Th2 biased responses to RSV infection. Abstract: Respiratory syncytial virus (RSV) is one of the leading causes of bronchiolitis in children, and severe RSV infection early in life has been associated with asthma development. Using a neonatal mouse model, we have shown that down-regulation of IL-4 receptor α (IL-4Rα) with antisense oligonucleotides in the lung during neonatal infection protected from RSV immunopathophysiology. Significant down-regulation of IL-4Rα was observed on pulmonary CD11b + myeloid dendritic cells (mDCs) suggesting a role for IL-4Rα on mDCs in the immunopathogenesis of neonatal RSV infection. Here, we demonstrated that neonatal CD11b + mDCs expressed higher levels of IL-4Rα than their adult counterparts. Because CD11b + mDCs mainly present antigens to CD4 + T cells, we hypothesized that increased expression of IL-4Rα on neonatal CD11b + mDCs was responsible for Th2 - biased RSV immunopathophysiology. Indeed, when IL-4Rα was selectively deleted from CD11b + mDCs, the immunopathophysiology typically observed following RSV reinfection was ablated, including Th2 inflammation, airway-mucus hyperproduction, and pulmonary dysfunction. Further, overexpression of IL-4Rα on adult CD11b + DCs and their adoptive transfer into adult mice was able to recapitulate the Th2-biased RSV immunopathology typically observed only in neonates infected with RSV. IL-4Rα levels on CD11c + cells were inversely correlated with maturation status of CD11b + mDCs upon RSV infection. Our data demonstrate that developmentally regulated IL-4Rα expression is critical for the maturity of pulmonary CD11b + mDCs and the Th2-biased immunopathogenesis of neonatal RSV infection.